The doctrine of double effect: reflections for a correct application - Falla Guirao de Guich, Miryam (2009)
The present article attempts to reflecto n how a correct application of “The doctrine of doublé effect” may be posible considering that an action may produce a doublé consequence, that is, a good one and a bad one. What is intended to demostrate is that when the doctrine is put into practice, the cause must be proportionally serious to tolerate the evil that will occur as a colateral effect in the name of goodness. It is not about choosing evil but it just tolerating it as a concurrent result of an action urgently  requiered